Pesantren as the Three Centers of Education Perspective of Ki Hadjar Dewantara - Taufikin Taufikin (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
The pros and cons of the full-day school system in Indonesia have occurred for a long time. However, the pesantren (boarding school), which uses more than a full day school system, is in fact more and more attractive to parents because it can educate their children more thoroughly. It turns out that the Ki Hadjar Dewantara (KHD) education concept also states that the boarding school system is the best for national education. With content analysis, KHD's documents are analyzed in this literature study, especially regarding the concept of education in the boarding school system. KHD tries to protect the nation's assets, namely children, through preserving their own cultural traditions and teaching values that are in accordance with the life of the nation and state through the three centers or three education centers, namely family, school, and community. To realize the success of the three centers of education in one place, KHD gave the idea that the boarding school system is the most ideal to be implemented for the character, intellectual and social manners.